2018
DOI: 10.1097/md.0000000000009429
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of an optimized blood management program in total hip and knee arthroplasty

Abstract: Little has been published on blood management in total hip and knee arthroplasty (THA and TKA, respectively) patients focusing on both hematopoiesis and hemostasis. Our aim was to explore the effectiveness and safety of an optimized blood management program in THA and TKA patients in a large, single-center, retrospective study.We retrospectively reviewed consecutive primary unilateral THA and TKA patients’ data at our institution through the National Health Database. They were divided into 3 groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…The efficacy of perioperative intravenous iron administration of (iron sucrose or iron isomaltoside) to reduce transfusion rates in knee or hip arthroplasty has been evaluated in one RCT and three observational studies (3574 patients) (Table ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The efficacy of perioperative intravenous iron administration of (iron sucrose or iron isomaltoside) to reduce transfusion rates in knee or hip arthroplasty has been evaluated in one RCT and three observational studies (3574 patients) (Table ).…”
Section: Resultsmentioning
confidence: 90%
“…More recently, in a large retrospective study, Zhang et al . showed that intravenous (20 mg/kg) plus topical (1 g) tranexamic acid administration resulted in very low ABT in hip or knee arthroplasty. Additional perioperative administration of intravenous iron sucrose (200 mg/48 h) and EPO (10 000 IU/day) to anaemic patients, rather than oral iron (150–300 mg/day), further reduced ABT in hip arthroplasty (3·9% vs. 7·2%; RR: 0·54, 95% CI: 0·35–0·82, P = 0·0035,) but not in knee arthroplasty (2·2% vs. 2·9%; RR: 0·74.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral or intravenous iron supplements (Shanghai UCB Trading Co., Ltd., Shanghai, China) and subcutaneous erythropoietin (Shenyang 3SBio Inc., Shenyang, China) were administered to patients with postoperative anemia according to the optimized blood management program. 12 The criterion of blood transfusion was set as a Hb level of <7 g/dL or 7 to 10 g/dL with symptomatic anemia according to the guidelines by the National Ministry of Health. 12…”
Section: Postoperative Care Protocolmentioning
confidence: 99%
“…12 The criterion of blood transfusion was set as a Hb level of <7 g/dL or 7 to 10 g/dL with symptomatic anemia according to the guidelines by the National Ministry of Health. 12…”
Section: Postoperative Care Protocolmentioning
confidence: 99%